In vivo assessment of an industrial waste product as a feed additive in dairy cows: Effects of larch (Larix decidua L.) sawdust on blood parameters and milk composition. Issue 3 (December 2015) - Tedesco, D.; Garavaglia, L.; Spagnuolo, M.S.; Pferschy-Wenzig, E.M.; Bauer, R.; Franz, C.
Highlights: Larch sawdust is a waste material rich in biologically active compounds. This study investigated the effects of larch sawdust on the health and milk composition of lactating dairy cows. Larch sawdust evidenced liver-beneficial potential. Larch sawdust is a candidate health-beneficial feed supplement. Abstract: When larch ( Larix spp . ) is processed in the wood industry, the sawdust is currently disposed of as waste or used as combustible material, even though it is rich in biologically active compounds. In this study the effect of larch sawdust supplementation on blood parameters as well as milk composition was examined in healthy mid-lactating dairy cows. Twenty-four multiparous Italian Friesian dairy cows were assigned to groups receiving either 300 g/day/cow of larch sawdust or a control diet, and treatments were continued for a 20 day period. Milk parameters were unaffected by treatment. A lower plasma total protein concentration was observed and can be attributed to a decrease in globulin concentration. A lower plasma urea concentration was also detected in the larch group. Moreover, biomarkers of liver function were influenced by the treatment. Total bilirubin was lower in larch-treated animals, and cholesterol tended to be lower. In addition, an interaction between day and treatment was observed for very low density lipoprotein. The concentration of other parameters, including reactive oxygen metabolites, superoxide dismutase, glutathione peroxidase and nitrotyrosine, did not differ between treatments. The observed benefits, together with the good palatability, make larch sawdust a promising candidate for the development of beneficial feed supplements for livestock. Further studies will be useful, particularly to evaluate its efficacy in different health conditions.